The rules, practice, and jurisprudence of international courts and tribunals - Giorgetti, Chiara (BRILL, 2012)
This book examines existing international disputes resolution institutions of both general and specific subject-matter jurisdiction. Uniquely, it assesses both procedural rules and essential case-law, making it relevant for both academics and practitioners in international law.